The Influence of Quality of Work Life, Work Environment and Religiosity on Organizational Citizenship Behavior with Job Satisfaction as a Mediator Variable - Tamam, Moh. Badrut; Soetjipto, Budi Eko; Murwani, F. Danardana (Graduate Program Magister Manajemen Pendidikan, 2024)
This study aims to analyze the effect of Quality Of Work Life, Work Environment, Religiosity on Organizational Citizenship Behavior (OCB) and analyze the mediating role of Job Satisfaction on OCB. This research is quantitative (survey). The type of data used is primary data obtained through the distribution of questionnaires. The respondents of this study were 124 employees of Malang City Digital Startup. Data analysis using descriptive analysis of PLS analysis with the help of SmartPLS application version 4. Based on research in the field, the results obtained are: Quality of work life, Work Environment and Religiosity has a significant positive effect on OCB through Job Satisfaction. The results of this study answer the hypothesis or research gap from the previous literature and deepen OCB employee research in the field of digital startups in the Malang City area. This research contributes to the development of knowledge related to Digital Start-up, Quality of Work Life, Work Environment, Religiosity, Job Satisfaction and OCB.